Progress in Landslide Research and Technology, Volume 1 Issue 2, 2022 - Alcántara-Ayala, Irasema; Arbanas, Željko; Huntley, David; Konagai, Kazuo; Mikoš, Matjaž; Sassa, Kyoji; Sassa, Shinji; Tang, Huiming; Tiwari, Binod (Progress in Landslide Research and Technology,, 2023)
This open access book provides an overview of the progress in landslide research and technology and is part of a book series of the International Consortium on Landslides (ICL). It gives an overview of recent progress in landslide research and technology for practical applications and the benefit for the society contributing to understanding and reducing landslide disaster risk. Prof. Irasema Alcántara-Ayala is a former Director and current Professor at the Institute of Geography of the National Autonomous University of Mexico (UNAM). She is a member of the UNDRR R-STAG of the Americas and an Editor of the ICL book series P-LRT. Prof. Željko Arbanas is the Vice President of the ICL for Europe. He is a professor at the Faculty of Engineering, University of Rijeka, Croatia. He is an Assistant Editor-in-Chief of the International Journal Landslides and the ICL book series P-LRT. Dr. David Huntley is Research Scientist with the Geological Sur vey of Canada and Open Learning Faculty at Thompson Rivers University, British Columbia. He is an Editor of the ICL book series P-LRT. Prof. Kazuo Konagai is a Professor Emeritus at the University of Tokyo and Principal Researcher of the ICL headquarters. He is an Assistant Editor-in-Chief of the ICL book series P-LRT. Matjaž Mikoš, Professor at the Faculty of Civil and Geodetic Engineering, University of Ljubljana, Slovenia, is the Chairman of the Global Promotion Committee of the International Programme on Landslides and Kyoto Landslide Commitment 2020. Prof. Kyoji Sassa is the Founding President and the Secretary General of the ICL and the Secretary General of the Kyoto Landslide Commitment 2020. He is the Editor-in-Chief of the International Journal Landslides and the ICL book series P-LRT. Dr. Shinji Sassa is the Head of Soil Dynamics Group and Research Director at Port and Airport Research Institute, National Institute of Maritime, Port and Aviation Technology, Japan. He is an Editor of the International Journal Landslides and the ICL book series P-LRT. Prof. Huiming Tang is the Vice President of China University of Geosciences (Wuhan) and a Chief Professor at the Faculty of Engineering. He is a full member of ICL, Chairman of the Engineering Geology commission of China and Vice President of IAEG. Prof. Binod Tiwari is the Vice President of the ICL for America. He is a professor of civil and environment engineering at the California State University, Fullerton California, USA. He is an Assistant Editor-in-Chief of the ICL book series P-LRT.